2013
DOI: 10.1016/j.jfma.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical pleurodesis for spontaneous pneumothorax

Abstract: Pneumothorax is defined as the presence of air in the pleural cavity. Spontaneous pneumothorax, occurring without antecedent traumatic or iatrogenic cause, is sub-divided into primary and secondary. The severity of pneumothorax could be varied from asymptomatic to hemodynamically compromised. Optimal management of this benign disease has been a matter of debate. In addition to evacuating air from the pleural space by simple aspiration or chest tube drainage, the management of spontaneous pneumothorax also focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 69 publications
0
37
0
3
Order By: Relevance
“…The recurrence rate seen after talc poudrage is comparable to that seen after mechanical pleurodesis [143][144][145]. Other sclerosing agents given via a chest tube have been used for prevention of pneumothorax, and include bleomycin dextrose, glucose 50%, iodine, tetracycline or talc slurry [146]. Tetracycline has also been used but is less efficacious than talc poudrage [116,147] and is no longer available in many countries [148].…”
Section: Indicationsmentioning
confidence: 99%
“…The recurrence rate seen after talc poudrage is comparable to that seen after mechanical pleurodesis [143][144][145]. Other sclerosing agents given via a chest tube have been used for prevention of pneumothorax, and include bleomycin dextrose, glucose 50%, iodine, tetracycline or talc slurry [146]. Tetracycline has also been used but is less efficacious than talc poudrage [116,147] and is no longer available in many countries [148].…”
Section: Indicationsmentioning
confidence: 99%
“…Instillation of chemical agents, doxycycline, and talc has been recommended in cases of prolonged air leakage. [3] Pleurodesis is an easy, safe, effective, and well-tolerated treatment for secondary pneumothorax [6,7,9,11] Some studies have reported the effectiveness of pleurodesis using a 50% glucose solution in treating pneumothorax with prolonged air leakage after a surgical procedure or chylothorax [12,14,15]. To my knowledge, only a few studies have investigated patients with secondary pneumothorax in whom surgery is contraindicated [13].…”
Section: Discussionmentioning
confidence: 99%
“…The main complications of conventional pleurodesis, such as pain and fever, [8,9] Present cases were obtained once with the use of a glucose solution, but it was unnecessary analgesics. In fact, the patient in Case 1 rejected to use OK-432 because of prior its side effects, despite it was effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations